Social skills in the professional docent formation - Acevedo Tovar, Luz Marina (2014)
This article deals with the importance of the learning pro-cess and the management of social skills in the context of integral education; in this context we consider it is impor-tant to characterize the docent because is the fundamental agent in the educational task. This study examines the pro-file of elementary education docents and high school do-cents, according to the following abilities: assertive beha-vior, and emotions and feelings management. The sample is constituted by docents that work in public and private schools; there are four instruments applied to the sample. Finally, the obtained results provide meaningful percenta-ges of non assertive behaviors, as well as a meaningful percentage of docents that declare an often inappropriate feelings and emotions management.